Tabot sebagai City Branding Kota Bengkulu - Johan Andi Wijaya (Jurnal Empirika, 2021)
This research is titled "Tabot As City Branding Of Bengkulu City". The problem of research is the process of forming tabot as a city branding of Bengkulu City. This research uses cultural studies approach by Stuart Hall. This research is a qualitative research with ethnographic research startegy. The analysis unit in this research is an organization, namely the Tourism and Culture Office of Bengkulu City. Data collection was obtained through in-depth interviews on 13 informants, observations of nonparticipant and documentation. The results of this study showed that tabot as the city branding of Bengkulu city was formed through the process of representation of tabot tradition into a tabot festival conducted by the Bengkulu city government. Bengkulu City Government makes tabot as a characteristic of Bengkulu City through a regulatory reproduction process to form tabot as the identity of Bengkulu City. The Government of Bengkulu wants to present Bengkulu as a religious city, has creativity, and a vibrant city that is depicted from the celebration of tabot festival, as well as as a reference for one of the cultural tourism cities.